Surgery for appendicular mass - Al-Samarrai Asal Y Izzidien (The Saudi Journal of Gastroenterology, 1995)
Two hundred and seventy-seven patients were admitted with acute appendicitis to KKUH during a 5 year period. There were 189 males (68%) and 88 females (32%). Of these,51 patients(18.4%) had appendicu-lar mass diagnosed clinically or under anaesthesia. Twenty five were males and twenty six females. All patients with appendicular mass underwent exploration and six were found to have abscess forma-tion.All patients had their appendix removed. There was no mortality. Three patients developed wound infection, one a pelvic collection and one had sub-acute intestinal obstruction, giving a complication rate of 9.8%. We feel a surgical approach for appendicular mass, in a specialised centre dealing with paediatric surgical patients, is a safe alternative to the classical textbook conservative approach. It also has the benefit of reducing the hospital stay and requires no readmission for interval appendectomy, for which many patients fail to return.